Staphylococcus cohnii spp urealyticus: relato de caso de um patógeno incomum - d'Azevedo, Pedro Alves [UNIFESP] (2008)
Coagulase-negative Staphylococcus has emerged as an important agent in nosocomial infections. In this study, we report a case of bacteremia associated with a central venous catheter, caused by Staphylococcus cohnii spp urealyticus that was isolated in blood cultures from a 53-year-old male patient who was admitted to a general hospital in the city of São Paulo. We discuss in this report the difficulty in routinely identifying this microorganism in the clinical microbiology laboratory. Staphylococcus cohnii spp urealyticus is a microorganism found in human skin as part of the normal microbiota, and it can cause serious infections in humans, in some situations.